(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Besides being a very particular hypothesis of personal data, genetic data also represents a precious resource for humanity. Hence, defining such data in light of circulation rules and data protection might bestow disproportionate power on the source-subject, thereby threatening to compromise the social value of genetic resources. Trying to overcome the dimension of individual belonging, it could therefore be useful to rediscover collective-solidarity as well as the category of common goods. However, the issue of establishing the actual ways of using and managing such a common resource remains pending – a task that can be entrusted to administrative law.